2012
DOI: 10.1093/jb/mvr145
|View full text |Cite
|
Sign up to set email alerts
|

The OsGEN-L protein from Oryza sativa possesses Holliday junction resolvase activity as well as 5'-flap endonuclease activity

Abstract: OsGEN-L has a 5'-flap endonuclease activity and plays an essential role in rice microspore development. The Class 4 RAD2/XPG family nucleases, including OsGEN-L, were recently found to have resolving activity for the Holliday junction (HJ), the intermediate of DNA strand recombination. In this study, we performed a detailed characterization of OsGEN-L, as a structure-specific endonuclease. Highly purified OsGEN-L was prepared as the full-length protein for in vitro endonuclease assays using various structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Most plants possess two putative GEN1/Yen1 homologs, GEN1 and SEND1 (Furukawa et al, 2003;Moritoh et al, 2005;Bauknecht and Kobbe, 2014), and in vitro studies of the Arabidopsis and rice proteins show that they can cleave HJ (Furukawa et al, 2003;Moritoh et al, 2005;Yang et al, 2012;Bauknecht and Kobbe, 2014). We thus isolated Arabidopsis mutants lacking GEN1 and/or SEND1 and analyzed their role in DNA repair and meiosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most plants possess two putative GEN1/Yen1 homologs, GEN1 and SEND1 (Furukawa et al, 2003;Moritoh et al, 2005;Bauknecht and Kobbe, 2014), and in vitro studies of the Arabidopsis and rice proteins show that they can cleave HJ (Furukawa et al, 2003;Moritoh et al, 2005;Yang et al, 2012;Bauknecht and Kobbe, 2014). We thus isolated Arabidopsis mutants lacking GEN1 and/or SEND1 and analyzed their role in DNA repair and meiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most plants possess two homologs of GEN1/Yen1: GEN1 and SEND1 (SINGLE-STRAND DNA ENDONUCLEASE1) (Furukawa et al, 2003;Moritoh et al, 2005;Bauknecht and Kobbe, 2014). Biochemical analyses in rice and Arabidopsis showed that the two proteins have similar biochemical activities and are able to process 59 flap, RF, as well as HJ structures (Furukawa et al, 2003;Yang et al, 2012;Bauknecht and Kobbe, 2014). In rice, GEN1 plays an essential role in pollen development (Moritoh et al, 2005), while SEND1 is preferentially expressed in proliferating tissues and is induced by UV and DNA damaging agents, suggesting a role in DNA repair (Furukawa et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…S3). The XPGI and N-terminal XPG domains are conserved in the Yen1/GEN1 subfamily (Moritoh et al, 2005;Yang et al, 2012), whereas the C terminus is highly variable. As the osgen1 mutation is present in the C terminus, the sterile phenotype suggests that this is important for OsGEN1 function.…”
Section: Identification Of the Osgen1 Mutantmentioning
confidence: 99%
“…It was reported that Yen1/GEN1 homologs from human, yeast, Caenorhabditis elegans, Arabidopsis (Arabidopsis thaliana), and rice (Oryza sativa) have the ability to cleave 59-flaps, replication forks (RFs), and HJs in vitro (Ip et al, 2008;Bailly et al, 2010;Yang et al, 2012;Bauknecht and Kobbe, 2014;Lee et al, 2015). The Yen1/GEN1 HJ resolution pathway shows a complicated interplay with other HJ resolution pathways and functional variation in different organisms.…”
mentioning
confidence: 99%
“…Some oligonucleotides were obtained from Dr. Y. Ishino (Kyushu University, Japan) and were described previously (39). TEMP90, TEMP70, TEMP50, TEMP30, and 49N were labeled with [␥- 32 P]ATP (PerkinElmer Life Sciences) using T4 polynucleotide kinase (Takara), and 500 fmol of labeled DNA was annealed with equimolar amounts of complementary oligonucleotide (5Ј end DNAs, 3Ј-TEMP/TEMP90 and d22/49N; 3Ј end DNAs, 5Ј-TEMP/ TEMP90 and d27/49N; dsDNAs, RTEMP90/TEMP90, RTEMP70/ TEMP70, RTEMP50/TEMP50, RTEMP30/TEMP30, and 49R/ 49N; fork DNA, F5-d42/49N) in annealing buffer (500 mM NaCl, 10 mM Tris-HCl (pH 8.0), and 1 mM EDTA) by gradual cooling to room temperature for 5 h following heating at 95°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%